2001
DOI: 10.1086/338499
|View full text |Cite
|
Sign up to set email alerts
|

[ITAL]Chandra[/ITAL] Exposes the Core-collapsed Globular Cluster NGC 6397

Abstract: We report results of the Chandra deep imaging observation of the closest post-core collapse globular cluster, NGC 6397. Some 25 sources are detected within 2 ′ of the cluster center of which ∼20 are likely cluster members with L x > ∼ 3 × 10 29 erg s −1 . The x-ray spectra suggest identifications with 1 quiescent low mass x-ray binary (qLMXB) detected by the thermal emission from its neutron star (NS) and 9 cataclysmic variables (CVs), 8 of which are identified in our deep HST imaging survey (reported separate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
179
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(192 citation statements)
references
References 18 publications
11
179
2
Order By: Relevance
“…The low luminosity and relatively hard X-ray spectrum of W29 are similar to those of U12 (the X-ray counterpart of NGC 6397A; Grindlay et al 2001b) and 47 Tuc J, both eclipsing MSP binaries (see Grindlay et al 2002). The X-ray spectrum of W29 can be best fit with a power law (photon index = 1:8 AE 0:6 when fixing N H to the nominal cluster value; 2 ¼ 1:55), and the luminosity in the 0.5-2.5 keV band is 7:8 Â 10 30 ergs s À1 .…”
Section: W29 and Chandra-hst Astrometrymentioning
confidence: 64%
“…The low luminosity and relatively hard X-ray spectrum of W29 are similar to those of U12 (the X-ray counterpart of NGC 6397A; Grindlay et al 2001b) and 47 Tuc J, both eclipsing MSP binaries (see Grindlay et al 2002). The X-ray spectrum of W29 can be best fit with a power law (photon index = 1:8 AE 0:6 when fixing N H to the nominal cluster value; 2 ¼ 1:55), and the luminosity in the 0.5-2.5 keV band is 7:8 Â 10 30 ergs s À1 .…”
Section: W29 and Chandra-hst Astrometrymentioning
confidence: 64%
“…The post-recycling exchange of a fresh main-sequence star into this binary is also consistent with the data and furthermore consistent with our picture of the dynamically evolving binary population in the NGC 6397 core. Additional evidence in support of such a picture for the core of NGC 6397 is presented by Grindlay et al (2001b), who find that another of the BY Dra candidates discovered by TGE01 may actually be a multiply exchanged millisecond pulsar (based on the X-ray properties).…”
Section: An Evolving Populationmentioning
confidence: 91%
“…Of particular importance is the primordial binary star population (Heggie 1975;Hut et al 1992), which provides a crucial internal energy source for the cluster by virtue of inelastic scattering encounters. Some of the more dramatic products of these encounters include recycled pulsars (Rappaport, Putney, & Verbunt 1989;Phinney 1996), low-mass X-ray binaries (Verbunt & Johnston 1996), cataclysmic variables (CVs; Di Stefano & Rappaport 1994;Cool et al 1995;Grindlay et al 2001aGrindlay et al , 2001b, and blue stragglers (Sigurdsson, Davies, & Bolte 1994;Lombardi, Rasio, & Shapiro 1996). Cool et al (1998, hereafter CGC98) and Edmonds et al (1999, hereafter EGC99) have reported the detection of a new stellar population near the center of the core-collapsed globular cluster NGC 6397.…”
Section: Introductionmentioning
confidence: 99%
“…However, the epoch in between our fourth and fifth epoch is not covered by the NUV observations, so we cannot tell whether the sources were indeed brighter in between the fourth and fifth epoch or not. Shara et al (2005) suggested that the CVs U17 (CV3 in Shara et al 2005, Grindlay et al 2001b) and U19 (CV2) underwent DN eruptions. U17 (CV3) was seen to brighten in optical WFPC2 data, but not in the STIS FUV data available at that time.…”
Section: Nuv Variabilitymentioning
confidence: 99%
“…Chandra X-ray observations have been carried out by Grindlay et al (2001a) and Bogdanov et al (2010), detecting 79 X-ray sources within the half-mass radius of this cluster. Shara et al (2005) used WFPC2 and STIS UV imaging and detected dwarf nova (DN) eruptions in two CVs that had previously been suggested to be magnetic systems (Grindlay et al 2001b) and which are usually not expected to show DN eruptions. Shara et al (2005) suggested that these two systems might be intermediate polars that occasionally undergo DN eruptions, which might explain the scarcity of DNs in GCs.…”
mentioning
confidence: 99%